Studi Kasus: Ketidaknyamanan Pada Ibu Hamil Dengan Intervensi Senam Kegel - Wahyuni, Sari; Nurlinda, Nurlinda; Komariah, Nurul; Rohaya, Rohaya; Kamalia, Rita (NURSING UPDATE : Jurnal Ilmiah Ilmu Keperawatan P-ISSN : 2085-5931 e-ISSN : 2623-2871, 2024)
Frequent urination is a common complaint among pregnant women, particularly during the first and third trimesters, due to hormonal changes and the enlarged uterus exerting pressure on the bladder. This complaint can disrupt the comfort and quality of life of pregnant women and increase the risk of urinary tract infections. One intervention to address this issue is Kegel exercises. This study aims to analyze midwifery care for a 35-week pregnant woman with complaints of frequent urination using a Kegel exercise approach. The case study was conducted on Mrs. P, G3P2A0 pregnant woman at 35 weeks of gestation, at PMB Tinti Halipah Palembang on October 21, 2023. Data collection included interviews, observations, physical examinations, and documentation using the SOAP method. The intervention consisted of education on the physiological changes of pregnancy, fluid intake management, Kegel exercise implementation, and recommendations to maintain genital hygiene to prevent urinary tract infection. The results of the intervention showed that Kegel exercises helped strengthen pelvic floor muscles, reduce complaints of frequent urination, and improve comfort during pregnancy. Mrs. P was able to understand and implement the recommended fluid intake patterns and consistently performed Kegel exercises, significantly reducing the frequency of complaints. The condition of both the mother and the fetus remained good until the final evaluation. .